HARMONISING NATIONAL ECONOMIC SOVEREIGNTY AND INTERNATIONAL TRADE STANDARDS THROUGH THE RECOGNITION OF THE CONSTITUTIONAL RIGHTS OF INDIGENOUS COMMUNITIES TO NATURAL RESOURCES - Abdul Razak Nasution; Muhammad Juang Rambe; Rahul Ardian Fikri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The application of extraterritorial non-tariff barriers within the international trade framework, such as the European Union Deforestation Regulation (EUDR), gives rise to jurisdictional conflicts regarding the principle of permanent sovereignty over the natural resources of developing countries. Such unilateral policies have implications for the vulnerability of the protection of the constitutional rights of Indigenous Peoples (IP) within the governance of commodity supply chains at the domestic level. This study aims to analyse the alignment of a state’s economic sovereignty with global environmental standards through the fulfilment of IP customary rights. Using a normative legal research method with legislative, conceptual, and policy analysis approaches, this study finds that legal mitigation of international market regulations is inadequate if it relies solely on a formal compliance approach within the Indonesian Sustainable Palm Oil (ISPO) instrument and the National Dashboard system. Legal loopholes resulting from procedural obstacles to establishing MHA status in regions risk legalising land tenure that is legally flawed for the sake of meeting certification requirements. Harmonisation of the legal system requires the enactment of specific legislation (lex specialis) on MHA, the establishment of Free, Prior and Informed Consent (FPIC) as an absolute prerequisite for business licensing, and the integration of indigenous territory mapping into the national geospatial database. This legal framework serves as a guarantee of domestic rights certainty whilst also functioning as a legitimate strategic diplomatic instrument in countering environmental protection justifications used as barriers to global trade.